Stereotype Level of Linguistic Concsiousnes: Socio- and Psycho-Linguistic Grounds - L. V. Matevosyan (Russian State Vocational Pedagogical University, 2015)
The linguistic consciousness is regarded as a multilevel system, its stereotype level being one of the structural bases. Applying a statistic analysis, the author justifies a reflex-driven nature of stereotype statements emphasizing their socio- and psycho-linguistic grounds. The paper describes a stereotype statement derivation, conditioned by language pragmatics, and focused on communication, which brings forth a need for standard. A stereotype statement development mechanism is based on a multiple repetition of a similar speech situation. As a result, communicative units used in such situations are perceived as steady correlated forms. Speech stereotypes, as many other standards, are less informative than non-stereotype forms. However, it does not undermine the significance of their studying, since they result from accumulation of socio-historical experience and knowledge.Given the mass communication, the process of identification and fixation of repeated common, emotional, and therefore, linguistic situations, is important and appropriate; and a list of such stereotype units can be subsequently used in the process of teaching foreign languages.